Frontal Networks Play a Role in Fatigue Perception in Multiple Sclerosis. - Pardini, Matteo; Bonzano, Laura; Mancardi, Giovanni Luigi; Roccatagliata, Luca (Behavioral Neuroscience, 2010)
Fatigue, an overwhelming lack of physical or mental energy, is a common complaint in patients affected by multiple sclerosis (MS). Although different mechanisms have been proposed to explain MS-related fatigue, injury of distinct anatomical networks seems to be relevant in fatigue etiology. Particularly, theories point to fronto-striatal network pathological changes as a possible neural basis of fatigue. To investigate the role of fronto-striatal white matter structural alterations in fatigue perception we prospectively recruited 40 relapsing remitting patients with MS and 15 healthy controls. In patients with MS, fatigue was assessed using a validated measure, the Modified Fatigue Impact Scale (MFIS; Kos et al., 2005). Brain MRI scans were acquired for each subject enrolled with diffusion tensor imaging. Diffusion tensor data were correlated with MFIS scores using voxel-wise analysis of fractional anisotropy maps and fiber tractography algorithms. A significant cluster of voxels correlating with fatigue scores located in the deep left frontal white matter was identified. Fiber tractography revealed the cluster to be included in a complex fronto-frontal, fronto-striatal, fronto-occipital, and fronto-limbic network. Structural properties of the traced white matter fiber bundles correlated with fatigue perception and patients with clinically relevant fatigue were found to present reduced white matter integrity in the aforementioned tracts compared to those with lower levels of fatigue. Our observations show a significant involvement of different frontal networks in the pathophysiology of fatigue, thus accounting for the multifaceted nature of this disabling symptom.